On geopolitics and education: Interventions, possibilities, and future directions. Issue 9 (27th April 2020) - Nguyen, Nicole
Abstract: In this article, I survey the rapidly developing literature on the symbiotic relationship between the education sector and geopolitics. Scholars across disciplines increasingly have studied how schools are implicated in and affected by broader geopolitical goals, particularly related to territorial security and national defense. Given the range of disciplinary interventions from international relations to education studies, discussions on the school‐geopolitics nexus often have been isolated and placed in relationship to other disciplinary conversations, forestalling rich cross‐disciplinary engagements to advance theorizations on the relationship between education and geopolitics. This review article, therefore, places studies on schools and geopolitics in conversation with each other and plots future directions for this emerging subfield. In doing so, I call on geographers to further engage the multi‐scalar analytics of feminist geopolitics, which can generate a more nuanced understanding of the school‐geopolitics nexus by more fully accounting for how geopolitical processes are differentially experienced, negotiated, and contested and for how the education sector itself maintains its own internal logics and contradictions irreducible to the external forces exerted on it.